(untitled) (Bangladesh Pharmaceutical Journal, 2018)
The present study is based on preparation of sustained release matrix tablets of tolterodine tartrate (for overactive bladder treatment) using guggul resin. Tolterodine tartrate is a highly soluble drug, to increase the duration of action the release of the drug has to be sustained. Natural resin is used as a polymer to sustain the release of drug, which was isolated from guggul gum by petroleum ether. Natural polymers are economical, biodegradable and can be chemically modified. Different ratios of drug and guggul resin were tried in the formulation of sustained release matrix tablets of tolterodine tartrate. Wet granulation technique was adopted for preparation of tolterodine tartrate granules, showed good flow properties and compressibility. The fabricated tablets were evaluated for various physicochemical characteristics and in vitro release studies like hardness, thickness, weight variation, friability, drug content and content uniformity were found to be within the limits. The drug release of optimized formulation (F6) was fitted to various kinetic models and the R2 value is 0.988 and the n value of drug release is 0.787. Therefore, the drug release follows zero order with non-fickian diffusion. The mechanism of drug release involves erosion and diffusion. Stability studies were performed for the optimized formulation as per ICH guidelines climatic zone III and were found to be stable with insignificant changes in physicochemical characteristics and in vitro release studies. Bangladesh Pharmaceutical Journal 21(1): 24-34, 2018